Guglielmo Cinque. 2020. The Syntax of Relative Clauses: A Unified Approach. Cambridge: Cambridge University Press. 414 pp. (Bucharest Working Papers in Linguistics, 2024)
Guglielmo Cinque’s monograph, The Syntax of Relative Clauses: A Unified Analysis, is a comprehensive examination of the structures of relative clause (RC) across languages, with the goal of elucidating the underlying foundation of all RCs through a unified analysis. His main proposal is that double-headed structures with an external head in the main clause and an internal head in the RC is the base structure for all RCs.